TRI HITA KARANA MENINGKATKAN KUALITAS MODAL MANUSIA DARI PERSFEKTIF KESEHATAN - I Wayan Artana (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2014)
Human capital contains the values found in the human beings themselves. Human capital has a value that canbe used to live their life to become more comfortable. The level of health is a very important human capital as afundamental support to be able to reflect other values in order to achieve successful society and individuals. Healthas defined by the World Health Organization (WHO) which initially defined that healthy means to be physically,psychologically, socially healthy, and free of defects. However, It has been now added with spiritually healthy. Thehealth of human capital is not only affected by genetics, health care facilities and infrastructure, as well as theenvironment, but also strongly influenced by the behavior or culture of human capital themselves, as well as theculture of the group in which human capital is located. Culture of Tri Hita Karana (THK) can improve the characterof human capital by means of improving their health values.